2022
DOI: 10.1080/14786419.2022.2101050
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Trichomonas vaginalis activity of essential oils extracted from Caatinga Myrtaceae species and chemical composition of Eugenia pohliana DC.

Abstract: The current trichomoniasis treatment options are scarce and the emergence of drug-resistant isolates points the need for new therapeutical alternatives. In this study the anti-Trichomonas vaginalis activity of essential oils obtained from Myrtaceae occurring in Caatinga, a plant family with potential antiparasitic activity, was showed. The essential oils varied in their capacity to kill ATCC and fresh clinical isolates, which was associated with heterogeneity and different patterns of endosymbiosis. Essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Thus, new drugs for the treatment of trichomoniasis are highly needed, and natural products have gained prominence as therapeutic alternatives. Previous studies have shown that essential oils from Myrtaceae species have potential against T. vaginalis [31]. Our results corroborate with these studies and point to EOSC as promising in combating T. vaginalis (IC 50 : 88.2 µg/mL), highlighting the need for studies using α-pinene against metronidazole-sensitive isolates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, new drugs for the treatment of trichomoniasis are highly needed, and natural products have gained prominence as therapeutic alternatives. Previous studies have shown that essential oils from Myrtaceae species have potential against T. vaginalis [31]. Our results corroborate with these studies and point to EOSC as promising in combating T. vaginalis (IC 50 : 88.2 µg/mL), highlighting the need for studies using α-pinene against metronidazole-sensitive isolates.…”
Section: Discussionsupporting
confidence: 90%
“…Trichomonads in the logarithmic growth phase exhibiting > 95% of normal motility and morphology were inoculated in fresh TYM for assays. The anti-T. vaginalis activity of EOSC was evaluated in vitro at concentrations ranging from 500 to 15.6 µg/mL, as described by Menezes et al [31]. The serial diluted EOSC (50 µL) was added to 96-well microplates with 2.0 × 10 5 trophozoites/mL suspensions (150 µL).…”
Section: Anti-trichomonas Vaginalis Activitymentioning
confidence: 99%